تفعيل دقة بيانات التكلفة الصناعية غير المباشرة للوحدة الإنتاجية في المؤسسات الإقتصادية ذات المزيج الإنتاجي غير المتجانس - جعارة, أسامة عمر (Université de M'sila, 2011)
It has been observed from reviewing many previous studies that the growing role of management accountant lead to the development of concepts of cost accounting activity, and show the relationship between the non-homogeneity of the mix of manufacturing cost and the indirect cost in conditions of uncertainty. The aim of this study was to investigate the nature of this relationship and the development of differnet entrance approach of the role of cost accounting systems by addressing the problem of allocation of indirect costs when the production mix is not uniform, leading to reduce the total cost charged to each particular activity. To prove the hypotheses of the study, the researcher used the appropriate theory and quantitative methods (statistical) and concluded that the relationship between the level of production costs and the nonhomogeneous mixture is a direct correlation, and the entrance to the application of cost accounting activity to achieve the company has many advantages.